Genotypic variability and relationships of Sorghum bicolor accessions from Java Island, Indonesia based on IRAP markers - Ika Nugraheni Ari Martiwi; Laurentius Hartanto Nugroho; Budi Setiadi Daryono; Ratna Susandarini (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Martiwi INA, Nugroho LH, Daryono BS, Susandarini R. 2020. Genotypic variability and relationships of Sorghum bicolor accessions from Java Island, Indonesia based on IRAP markers. Biodiversitas 21: 5637-5643. Sorghum (Sorghum bicolor (L.) Moench) is a multifunctional crop with high adaptability to various habitats and thus it is important to assess the genotypic variability of this crop species. This study aimed to reveal the genotypic variability and relationships of sorghum accessions using inter-retrotransposon amplified polymorphism (IRAP) molecular markers. Twenty-three sorghum accessions were collected from smallholder farmers in three provinces of Java Island during the 2019 planting season. The IRAP profiles generated using 10 primer combinations produced 233 scorable bands, with degree of polymorphism 75-96.9%. Cluster analysis using the neighbor-joining (NJ) method showed the formation of three groups corresponds to geographic origin of samples. The NJ dendrogram structure indicated high genotypic variability, and was supported by distribution pattern of accessions on the scatterplot constructed using principal coordinate analysis. The grouping of accessions did not correspond to classification of botanical races. Each group recognized from cluster analysis and principal coordinate analysis consisted of various races namely Bicolor, Guinea, Caudatum, and Kaffir. The fact that each group consisted of various botanical races indicated local adaptation and the maintenance of genotypic identity through farmers’ selection in traditional cultivation practices. It could be concluded, therefore, that geographical proximity and the practice of seed exchange between different regions showed considerable influence on the genotypic relationships of sorghum accessions.